Inoculation of Safety in Healthcare - Dobovšek, Bojan; Slak, Boštjan (Medicine, Law & Society, 2017)
The purpose of this paper is to analyse - through a prism of informal institutions - the role and importance of security in healthcare and the manner in which healthcare sector copes with security threats in postmodern society. We note that bad informal institutions are differently reflected in Slovenia. In the forefront are the problems of systemic corruption, various forms of clientelism and nepotism. This is (in)directly reflected in the (lack of) quality of Slovenian healthcare system. Inadequate public procurement system and conflicts of interest in healthcare sector are causing inferior quality of the healthcare system, while informal institutions in politics and economics are weakening Slovenian economy, consequently affecting the funding of Slovenian healthcare system which is also undermined by the financial crisis. Additionally, globalisation, which has a (negative) impact on human health, has caused the importation of improper business practices into healthcare system. It is therefore necessary to develop a preventive action that will inoculate the idea of a safe country for the benefit of people and not for the benefit of bad informal networks.
Keywords: Bad informal institutions; corruption; health systems; security